Journalist Protection on the Battlefield Under the International Humanitarian Law: Russia-Ukraine War - Gunawan, Yordan; Budiman, Arif; Fauziah, Nafiza; Syamsudin, Wa Ode Fithrah Az-zalia (Unissula, 2023)
The work of journalists on the battlefield is a tough duty with all the consequences and the threat of death that can occur at any time. This also happen to the journalist in the war between Russia and Ukraine. The case of two journalist of Fox News who were killed outside the capital city Kiev because the vehicle they were traveling in was shot in the city of Horenka. The purpose of this study is to find out whether the rights of journalists on the battlefield, especially in the conflict between Russia and Ukraine, can be protected by the existence of International Humanitarian Law (IHL). The method used is doctrinal and hermeneutic with data collection techniques, namely document studies and